Shaping the future aspirational leadership in India and beyond - Maira, Arun (John Wiley& sons, 2002)
"Looking at India's economic transformation of late, Arun Maira, Chairman of The Boston Consulting Group in India, addresses key factors that will affect companies investing there. Getting to the root of India's problems, he uses techniques of scenario thinking and organizational learning to guide the reader through the complex structures of Indian business and society. He examines the breadth of the problems facing the country, without losing sight of the importance of the human component. This book provides solutions that require many groups with conflicting interests to work together, encouraging action by citing successes that use this collaborative approach and the benefits that they would entail for the future of India's economy. Weaving throughout the book is also a close examination of leadership issues, exploring a new approach to change that can be adopted by leaders in emerging nations around the world." "Shaping the Future explains how the diverse elements of society in India, and any emerging nation, can work together to mold a better future."--BOOK JACKET.